KAJIAN PRODUKSI BIOINSEKTISIDA DARI Bacillus thuringiensis subsp israelensis PADA MEDIA TAPIOKA - Abdul Aziz Darwis, Khaswar Syamsu dan Ummi Salamah (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTBacillus thuringiensis subsp israelensis (B.t.i)  as one  of the Bacillus thuringiensis  (B.t) species produces crystal protein  called delta endotoxin. As other B.t  crystal protein, this crystal  is specifically toxic to mosquitoes and blackflies.  This research  of B.t.i fermentation  used tapioca as carbon source and urea as nitrogen source.  The composition of media fermentation used were 0.5%, 1.0%, 1.5%, 2.0%, 2.5% and 3.0% of  tapioca, and 1% urea.  The result shows that B.t.i was able to grow in all treatment units.  Bioassay shows that the best performance was  obtained from media with 2.0% tapioca.Key words: Bacillus thuringiensis, tapioca